The western end of the Avalon Zone in southern New Brunswick - Currie, K. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1988)
The western end of the Avalon zone of southern New Brunswick displays a history extending from middle Proterozoic to Triassic lime. About 620 Ma magmatism above a Late Prccambrian subduction zone emplaced volcanic rocks and plutons into an orthogneiss-platformal sequence basement which had been modified by mafic intrusion and thermal metamorphism about 780 Ma. About 565 Ma a bimodal sheeted dyke complex accompanied by bimodal volcanism and high-level granite was emplaced into a major mylonile zone during minor spreading or transtension. Shallow water clastic marine sediments accumulated during Cambro-Ordovician lime. From Silurian to mid-Devonian, die northwestern part of the zone subsided along steep faults which served as conduits for bimodal igneous activity. Strong Carboniferous deformation along the Bay of Fundy affected the interior of the lerrane only slightly, if at all. Acadian and Taconic orogenies had little effect on this region, which acted as a relatively stable crystalline block during the Paleozoic. The exposed rocks may form a "welt" on continuous basement of similar character, which disappears north-westward heneaih younger formations by down-stepping on faults, and south-eastward beneath overriding allochihons.